Paleogeographic evolution of the Lower Yangtze region and the break of the "platform-slope-basin" pattern during the Late Ordovician - Chen, Qing; Fan, Junxuan; Zhang, Linna; Chen, Xu (Science China Earth Sciences, 2018)
Wide distribution of the black shales and diversification of the graptolite fauna in South China during the Late Ordovician resulted from its unique paleogeographic pattern, which was significantly affected by the paleogeographic evolution of the Lower Yangtze region. In the study, 120 Upper Ordovician sections from the Lower Yangtze region were collected, and a unified biostratigraphic framework has been applied to these sections to establish a reliable stratigraphic subdivision and correlation. Under the unified time framework, we delineate the distribution area of each lithostratigraphic unit, outline the boundary between the sea and land, and reconstruct the paleogeographic pattern for each graptolite zone. The result indicates that, with the uplift and expansion of the 'Jiangnan Oldland' in the beginning of the late Katian, the oldland extended into the Yangtze Sea gradually from south to north, which finally separate the Jiangnan Slope and the Yangtze Platform. Consequently, the longstanding paleogeographic pattern of "platform-slope-basin" in South China was broken. The paleogeographic change led to sedimentary differentiation among the two sides of the 'Jiangnan Oldland' during the Late Ordovician. This event also led to the closure of the eastern exit of the Upper Yangtze Sea, and formed a semi-closed, limited and stagnant environment for the development of the organic-rich black shales during the Late Ordovician. The major controlling factors of these paleogeographic changes in the Lower Yangtze region were not consistent from the Katian to the Hirnantian. In the late Katian, the sedimentary differentiation between the east and west sides mostly resulted from regional tectonic movement - the Kwangsian Orogeny. However, during the Hirnantian, the whole Yangtze region became shallower, which was mostly influenced by the concentration of the Gondwana ice sheet and the consequent global sea level drop.